PENURUNAN KADAR CHEMICAL OXYGEN DEMAND (COD) PADA LIMBAH CAIR LAUNDRY ORENS TEMBALANG DENGAN BERBAGAI VARIASI DOSIS KARBON AKTIF TEMPURUNG KELAPA - Fransiska Vony Wicheisa; Yusniar Hanani Darundiati; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
COD measurement results in Laundry Orens are greater than quality standards according to the Central Java Regulation No.5 of 2012 (> 100 mg / lt) which are 249, 773, and 558mg / lt. Laundry liquid waste with high COD levels can cause environmental pollution. The purpose of this study was to determine the decrease in COD levels using coconut shell activated carbon. This type of research is quasi experimental with pretest-posttest with the control group design. The sample in this study amounted to 36 samples with 4 treatments (200; 300; 400; 500 gr / lt) with 6 repetitions. Samples are taken from the washing machine outlet pipe. Data analysis using one way ANOVA test showed that there was a decrease in liquid COD levels with a variety of activated carbon doses (p-value <0.05). Anova test results followed by the LSD method showed that the group between dose variations had a significant difference in reducing COD levels of laundry laundry waste (p <0.05), namely the control group with each treatment group and group 200 with 500 gr / lt. The average decrease in COD levels after treatment of 860mg / lt was 406mg / lt (47.13%) for a dose of 200gr / lt; 473mg / lt (55.22%) for a dose of 300gr / lt; 536.16mg / lt (62.33%) for a dose of 400gr / lt; and 587.83 mg / lt (68.37%) for a dose of 500 g / lt. The conclusion of this study was that coconut shell activated carbon was able to reduce COD levels with the highest decrease up to 68.37%.